Central vascular catheters versus peripherally inserted central catheters in nurse anesthesia. A perspective within the Greek health system. - Konstantinou, Evangelos A; Karampinis, Dimitrios F; Mitsos, Aristotelis P; Konstantinou, Maria I; Mariolis-Sapsakos, Theodoros; Kapritsou, Maria; Stafylarakis, Emmanuil; Katsoulas, Theodoros; Elefsiniotis, Ioannis (J Vasc Access, 2013)
PURPOSE: We present a study comparing the insertion of central vascular catheter (CVC) and peripherally inserted central catheter (PICC) by an anesthesia nurse at 2 Greek University Hospitals. METHODS: Eighty patients, aged 20-80 years, were enrolled in the study. Patients were divided into 2 groups. In group A (41 patients), a CVC was inserted in the internal jugular vein. In group B (39 patients), a pressure-injectable PICC was inserted in the basilica vein. RESULTS: Correlations between the methods applied, the patients' characteristics, the procedures' characteristics and the overall satisfaction scores for each procedure were examined. The final results show that the patients of group B (PICC method) were more satisfied with the procedure than the patients of group A (CVC method), at the statistical significance level of a=0.01. Also, according to the results of the analysis, the PICC method offers significantly more comfort and relative satisfaction than the CVC method, at the statistical significance level of a=0.01. The satisfaction scores of "physicians" were statistically more significant, at a=0.01, for the patients of group A (classic CVCs) mainly because of the insufficient flow rate of the PICCs when compared with the CVCs and especially if one considers the fact that the physicians did not have any experience with the PICC method at all. CONCLUSIONS: PICCs under ultrasound guidance constitute the solution of choice for patients and they definitely surpass the CVCs focusing mainly on the improvement of the quality of life and the satisfaction of patients.
Keywords: Adult; Aged; Aged, 80 and over; Attitude of Health Personnel; Catheterization, Central Venous; Catheterization, Peripheral; Central Venous Catheters; Female; Greece; Hospitals, University; Humans; Jugular Veins; Male; Middle Aged; Nurse Anesthetists; Patient Satisfaction; Quality of Life; Ultrasonography, Interventional; Young Adult